2010
DOI: 10.1021/ic101275m
|View full text |Cite
|
Sign up to set email alerts
|

NMR Spectroscopic Evidence for the Intermediacy of XeF3 in XeF2/F Exchange, Attempted Syntheses and Thermochemistry of XeF3 Salts, and Theoretical Studies of the XeF3 Anion

Abstract: The existence of the trifluoroxenate(II) anion, XeF3 -, had been postulated in a prior NMR study of the exchange between fluoride ion and XeF2 in CH3CN solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…[20] TheTshape for both XeF 3 À and CsF 3 is not al ocal minimum, while the Ys hape is. [20][21][22][23] Thee nergy of this minimum is about 32 kcal mol À1 (26 kcal mol À1 by DFT) above the asymmetric structure mentioned above.F inally,t here is ap yramidal C 3v isomer,4 6kcal mol À1 (38 kcal mol À1 at the PBE0 level) higher in energy.T he Tand Ys haped isomers are closed-shell singlets,w ith 83 %a nd 90 %c ontribution, respectively,f rom the leading configura-tion. In contrast, the pyramidal CsF 3 has an open-shell singlet as the ground state.…”
Section: Methodsmentioning
confidence: 75%
See 1 more Smart Citation
“…[20] TheTshape for both XeF 3 À and CsF 3 is not al ocal minimum, while the Ys hape is. [20][21][22][23] Thee nergy of this minimum is about 32 kcal mol À1 (26 kcal mol À1 by DFT) above the asymmetric structure mentioned above.F inally,t here is ap yramidal C 3v isomer,4 6kcal mol À1 (38 kcal mol À1 at the PBE0 level) higher in energy.T he Tand Ys haped isomers are closed-shell singlets,w ith 83 %a nd 90 %c ontribution, respectively,f rom the leading configura-tion. In contrast, the pyramidal CsF 3 has an open-shell singlet as the ground state.…”
Section: Methodsmentioning
confidence: 75%
“…As econd structure derives from a D 3h star-shaped molecule.S uch as pecies would share the electronic characteristics of the isoelectronic (and known [20,21] )X eF 3 À ion in being ac lassic Jahn-Teller system. Tw oelectrons would occupy an e orbital, with deformations to Tand Ys hapes expected.…”
Section: Methodsmentioning
confidence: 99%
“…Alex mentorship was not limited exclusively to magnetic resonance, but it extended to diverse topics of physical chemistry at large, drawing from his outstanding foundations and intuition in physical science in general as well as from his undergraduate double major in mathematics and chemistry, recognized early on with a Governor General's silver medal. The list of Alex's contributions in this respect is too long to be included here, but a few representative examples range from the help he provided for non‐trivial calculations of activation barriers in the rapid exchange between F − anion and XeF 2 to his critical assistance in measuring kinetic isotope effects . Alex's physico‐chemical intuition came to light also in his illuminating remarks during students’ presentations, which he typically found the time to attend.…”
Section: The Educatormentioning
confidence: 99%
“…The low-temperature (À173 1C) X-ray crystal structures showed that the NgF 2 ligands are coordinated trans to the F atoms of BrOF 2 + with the AsF 6 À anion coordinated trans to O. 6 The enthalpy of activation for this exchange, DH z , has now been determined by use of single selective inversion 19 (Ng = Kr, Xe; M = As, Sb, Bi) were assigned with the aid of quantum-chemical calculations by modeling the gas-phase ion pairs. The [BrOF 2 ][AsF 6 ]ÁXeF 2 complex was also characterised by Raman spectroscopy.…”
mentioning
confidence: 97%
“…The KrF 2 compound is the first example of KrF 2 coordinated to a main-group centre to have been characterised by X-ray crystallography (Fig. The [BrOF 2 ][AsF 6 ]ÁXeF 2 complex was also characterised by Raman spectroscopy. The solid-state Raman spectra of [BrOF 2 ][AsF 6 ]Á2NgF 2 (Ng = Kr, Xe) were assigned with the aid of quantum-chemical calculations.…”
mentioning
confidence: 99%